UPAYA MENCEGAH PIUTANG MACET BERBASIS PENDEKATAN PENGENDALIAN INTERNAL - Sugiyanto Sugiyanto; Wahyudin Wahyudin; Rahmina Puspa Aliza Ridwan; Lia Juhriah Lukitawati (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2022)
Abstract Cooperative members can improve their economic situation through their work in the organization. The Official Employee Cooperative is a multi-purpose cooperative that operates in various industries. Members of the Service Employees Cooperative are members of the Cooperative. This study aims to find out how the cooperative's internal control of receivables reduces bad debts by understanding how non-performing loans arise, the causes that cause uncollectible accounts, and the cooperative's internal control of bad debts and uncollectible accounts. A descriptive qualitative approach was used. Based on the results of this study, internal control in reducing bad debts for employees has been implemented, but has not been efficient, resulting in bad debts increasing every year.